Efficiency in the Use of Rice Farming Organic Inputs to Promote Food Security - Sukanteri, Ni Putu; Diah Yuniti, I Gusti Ayu; Suryana, I Made; Verrawati, Yenny (KnE Life Sciences, 2022)
Rice farming is highly developed in Tabanan Regency, which accounts for 27.04% of the agricultural land in Bali’s eight districts. Rice output is on the decline: 188,446 tons of rice were produced in Tabanan in 2018, 158,757 tons in 2019, and 142,846 tons in 2020. The use of inputs can influence farm productivity. Rice farmers have started to switch to using organic inputs such as fermented organic fertilizers through input processing technology innovations, and to using vegetable pesticides to combat disease. Land owned by farmers is classified as narrow land. Farmers’ awareness of the importance of providing healthy food is a powerful motivator for using organic inputs in rice production. The focus of this research was to determine the efficiency of rice farming inputs to ensure food security. The research took place in Tabanan Regency, with five groups of farmers who use organic fertilizers to manage their farms. Data were analyzed using cost analysis to determine the amount of input used in farming, and acceptance analysis to determine the optimal amount of farm productivity and income. The farmers had low land, according to the findings. Farmers have not been able to use farm inputs according to the requirements of Indonesian national standards to create food security, so their use of inputs is inefficient. The results showed that farmers benefit from rice farming innovations. Keywords: Organic farming, input rice organic